Silk sericin-enhanced microstructured bacterial cellulose as tissue engineering scaffold towards prospective gut repair - Lamboni, Lallepak; Schäfer, Karl Herbert (Materials science & engineering. C, Materials for biological applications, 2019)
As a first step towards the production of functional cell sheets applicable for the regeneration of gut muscle layer, microstructured bacterial cellulose (mBC) was assessed for its ability to support the growth of enteric nervous system (ENS) and gut smooth muscle cells (SMCs). To improve the cellular response, mBC was modified with silk sericin (SS) which has renowned abilities in supporting tissue regeneration. While SS did not impair the line structures imparted to BC by PDMS templates, similarly to the patterns, it affected its physical properties, ultimately leading to variations in the behavior of cells cultured onto these substrates. Enabled by the stripes on mBC, both SMCs and ENS cells were aligned in vitro, presenting the in vivo-like morphology essential for peristalsis and gut function. Interestingly, cell growth and differentiation remarkably enhanced upon SS addition to the samples, indicating the promise of the mBC-SS constructs as biomaterial not only for gut engineering, but also for tissues where cellular alignment is required for function, namely the heart, blood vessels, and similars.